Hyperfunctioning Papillary Microcarcinoma Diagnosed by 124I PET/Ultrasound Fusion Imaging. (May 2019) - Seifert, Philipp; Gühne, Falk; Freesmeyer, Martin
Abstract : Abstract: A 49-year-old woman presented with a multinodular goiter, causing local symptoms and hyperthyroisdism. Besides a hypofunctioning benign nodule (TIRADS 3, benign in FNAC), the conventional diagnostic revealed another small hyperfunctioning nodule with suspicious ultrasound features (TIRADS 4C). To rule out a trapping-only nodule and topographical misalignments, a 124 I PET/ultrasound fusion was performed and confirmed elevated iodine uptake within the suspicious nodule. Further disseminated autonomous areas are suspected to be additionally responsible for the low TSH-level. Because of the local cervical symptoms and the hyperthyroidism, the patient underwent surgery. The small hyperfunctioning nodule turned out to be a classic papillary microcarcinoma.